Feminine spirituality through an unknown catalan illuminated Book of Hours illuminated around 1500 - Planas, Josefina (Eikón / Imago, 2026)
Towards the last decade of the 15thcentury, was elaborated an exquisite book of hours for a lady. The manuscript, written in Latin with Catalan rubrics in the Roman use is kept in a private collection (Barcelona, Patrimoni artistic Fundació “La Caixa”). This book of hours was left unfinished and contains a good amount of decorated initials, accompanied by floral decoration or even a kind of marginal ornamentation with flowers, birds and human figures that acquire a more naturalistic dimension in some specific folios, in agreement with aesthetic proposals of the Wiener Master of Mary of Burgundy, aspect of which the last one was unknown in Catalonia. The full-page illustrations are seven in total and were made in grisaille with dashes of blue. The calendar includes celebrations typical of Barcelona. It has an office dedicated to the Guardian Angel (f. 211r) and amidst the Suffrages there is the prominent figure of Mary Magdalene (f. 235r), a model of contemplative woman for the theologians and moralists of the time. This study analyzes a manuscript that is practically unknown to researchers.